2021
DOI: 10.1002/anie.202104790
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Visible Light in Low‐Band‐Gap C4N‐Derived Responsive Bifunctional Air Electrodes for Solar Energy Conversion and Storage

Abstract: We report facile synthesis of low-band-gap mesoporous C 4 Np articles and their use as responsive bifunctional oxygen catalysts for visible-light-sensitive (VLS) rechargeable Zn-air battery (RZAB) and polymer-air battery (RPAB). Compared to widely studied g-C 3 N 4 ,C 4 Nshows asmaller band gap of 1.99 eV,with alarger photocurrent response,and it can function as visible-light-harvesting antenna and bifunctional oxygen reduction/evolution (ORR/OER) catalysts,e nabling effective photocoupling to tune oxygen cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 49 publications
(46 reference statements)
2
36
0
Order By: Relevance
“…To expand the light harvesting from UV to the visible light region, a low-band-gap C 4 N polymer has been introduced as the PE to modulate oxygen catalysis. The C 4 N-enabled Zn-air battery shows a low charge voltage of 1.35 V under visible light, corresponding to a high energy efficiency of 97.78% [141]. This PE can also be applied in visible-light-responsive polymer-air cells for improved device performance.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 94%
“…To expand the light harvesting from UV to the visible light region, a low-band-gap C 4 N polymer has been introduced as the PE to modulate oxygen catalysis. The C 4 N-enabled Zn-air battery shows a low charge voltage of 1.35 V under visible light, corresponding to a high energy efficiency of 97.78% [141]. This PE can also be applied in visible-light-responsive polymer-air cells for improved device performance.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 94%
“…[ 8 ] The elemental analysis (EA) indicates that the molar ratio of C to N atoms is about 4:1, proving an empirical formula of C 4 N (Table S1, Supporting Information). Fourier transform infrared (FTIR) spectrum of C 4 N in Figure 1g shows a characteristic peak at ≈1612 cm –1 ascribed to the stretch vibration of CN in pyrazine rings, [ 9 ] while a similar CN signal at ≈1612 cm –1 is also detected in the FTIR spectrum of C 4 N@TiO 2 NR, once again verifying the successful formation of C 4 N on the TiO 2 NR surface. This result is also consistent with X‐ray photoelectron spectroscopy (XPS) analysis.…”
Section: Resultsmentioning
confidence: 74%
“…Distinct from well-studied g-C 3 N 4 , most recently, Yu et al designed low-band-gap mesoporous C 4 N, particles, which showed an obvious enhancement for both oxygen reduction and evolution reactions under light illumination as depicted above. 88 Bettina. V. Lotsch et al designed a 2D cyanamide functionalized polyheptazine imide (NCN-PHI) as one single material for solar energy conversion and electrochemical energy storage.…”
Section: Types Of Pes Materials and Its Design Principlesmentioning
confidence: 99%